First trimester maternal exposures to endocrine disrupting chemicals and metals and fetal size in the Michigan Mother–Infant Pairs study. (30th January 2019) - Goodrich, Jaclyn M.; Ingle, Mary E.; Domino, Steven E.; Treadwell, Marjorie C.; Dolinoy, Dana C.; Burant, Charles; Meeker, John D.; Padmanabhan, Vasantha
Abstract: Exposures to endocrine disrupting chemicals and metals are near ubiquitous worldwide, and their potential impact on children is a major public health concern. This pilot study was designed to characterize exposures to phthalates, phenols and metals among pregnant women in the first trimester, and to examine associations with fetal biometrics and birth weight. A total of 41 chemicals and elements were analyzed in urine from 56 mothers with full-term newborns from the Michigan Mother–Infant Pairs study. Bivariate analyses identified predictors of exposure biomarkers. Associations between birth weight, Fenton z -scores and second trimester fetal biometrics with toxicants were examined via multivariable linear regression. An average of 30 toxicants were detected in maternal urine. Fast food consumption was associated with several phthalate metabolites, phenols and metals, and canned food consumption with bisphenol F ( P <0.05). Mono (3-carboxypropyl) phthalate was significantly associated with higher birth weight and Fenton z -score while the opposite was observed for bisphenol S. Estimated femur length from ultrasonography was significantly inversely associated with arsenic, barium and lead. While limited by sample size, this study is one of the first to evaluate birth outcomes with respect to emerging endocrine disrupting chemicals and to examine associations between toxicants and fetal biometrics. Exposure assessment was provided by the National Institute of Environmental Health Sciences' Children's Health Exposure Analysis Resource (NIEHS CHEAR), a resource available to children's studies with the goal of combining data across cohorts in an effort to characterize the impact of toxicants on child health from birth and beyond.